CONCEPTUAL PRINCIPLES REGARDING THE ASSESSMENT OF BUSINESS PROCESSES OF THE ENTERPRISE IN THE CONTEXT OF INNOVATIVE MANAGEMENT - Андрусів, Уляна Ярославівна; Черчата, Анжела Олексіївна; Зелінська , Галина Олексіївна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
It has been established that business processes are the basis on which the process-oriented management of enterprises based on innovative principles is grounded. It has been proven that for the effective management of business processes on an innovative basis, it is necessary to monitor and assess their state, since any changes in the conditions or results of the operation of business processes can be applied only when there are appropriate criteria and methods of their measurement. The article presents the conceptual principles for evaluating the business processes of enterprises in the context of innovative management of socio-economic systems. The process approach requires the company's management to take actions involving adaptation to changes and, as a result, improvement of business processes. The proposed methodology provides for the identification of "bottlenecks" of certain business processes by calculating weighted averages, integral and general indicators of effectiveness and efficiency. This makes it possible to assess the state of certain operational business processes of enterprises, as well as their totality, and to establish the priority of management actions regarding their improvement. It has been proven that an effective and relevant means of achieving the set goal is a process approach, which orients the activity of the enterprise on business processes, and the system of its management - on the management of each business process separately and their totality as a whole and/or within the limits of certain projects that implement enterprises. Evaluating the effectiveness and efficiency of business processes according to the specified criteria and indicators allows at a specific moment in time to monitor the current activity of the enterprise and evaluate the effectiveness of its functioning. Calculation of effectiveness indicators and individual business processes efficiency and the set of these business processes as a whole enables to obtain and aggregate data on the degree of achievement of both individual business processes goals and the set of these business processes synergistic goals. Information about the effectiveness and efficiency of business process execution is the basis for making management decisions by the management and application for operational control of business processes, analysis and improvement of the enterprise's activities on an innovative basis.